The Role of the Merah Putih Ranjeng Village Cooperative in Supporting the Economy of Micro-Entrepreneurs in Serang Regency, Banten - Vera Maria; Zulfa Kamila; Devi Yani; Nihayatuz Zahro; Maudi Lisdiana; Ilaf Praditya Dwiputra; Aidil Adhari; Ferdy Yulianto Simamora (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines the role of the Merah Putih Ranjeng Village Cooperative in supporting the economic activities of micro entrepreneurs in Serang Regency, Banten. The research employed an empirical qualitative design using a descriptive case study approach. Data were collected through in depth interviews, observation, and documentation involving cooperative management and micro entrepreneur members. The findings reveal that the cooperative contributes to economic empowerment by providing business necessities at more affordable prices, reducing production costs, and improving business profitability. The cooperative also facilitates access to market opportunities through collective activities, including bazaars that support product promotion and customer expansion. These functions enhance operational efficiency, strengthen business resilience, and support local economic development through cooperative participation. Despite these contributions, several institutional challenges remain evident, including limited capital resources, dependence on manager initiated funding, inadequate human resource capacity, and the incomplete implementation of savings and loan services and business mentoring programs. The study indicates that cooperative effectiveness depends not only on financial support but also on institutional capacity, governance readiness, and sustainable organizational development. Strengthening institutional structures and multi stakeholder collaboration is essential to maximize the cooperative's contribution to rural economic empowerment.